Self-Assembly of Metal Nanoclusters for Aggregation-Induced Emission - Jianxing Wang (International Journal of Molecular Sciences, 2019)
Aggregation-induced emission (AIE) is an intriguing strategy to enhance the luminescence of metal nanoclusters (NCs). However, the morphologies of aggregated NCs are often irregular and inhomogeneous, leading to instability and poor color purity of the aggregations, which greatly limit their further potential in optical applications. Inspired by self-assembly techniques, manipulating metal NCs into well-defined architectures has achieved success. The self-assembled metal NCs often exhibit enhancing emission stability and intensity compared to the individually or randomly aggregated ones. Meanwhile, the emission color of metal NCs becomes tunable. In this review, we summarize the synthetic strategies involved in self-assembly of metal NCs for the first time. For each synthetic strategy, we describe the self-assembly mechanisms involved and the dependence of optical properties on the self-assembly. Finally, we outline the current challenges to and perspectives on the development of this area.